Effet de Panicum maximum sur la productivité des femelles primipares durant le cycle de reproduction chez le cobaye (Cavia porcellus L.) - Danho, M.; Thys, E.; N'Goran D.V. Kouakou; Nogbou Assidjo, E.; Grongnet, JF. (Tropicultura, 2012)
Effect of Panicum maximum on Productivity of Primiparous Females during Reproduction Cycle in Guinea Pigs (Cavia porcellus L.). In Ivory Coast, Guinea pigs reared for meat (Cavia porcellus L.) are mainly fed with Panicum maximum. To assess the effect of the latter during pregnancy and lactation (RC) of these animals, primiparous dams were fed ad libitum, Panicum maximum alone during the RC (MOD1) or associated with pellets for rabbits during lactation (MOD2), or associated with pellets for rabbits during the last part of the pregnancy period and the lactation (MOD3), or associated with pellets for rabbits during the entire RC (MOD4). The number of corpora lutea per female was 1.3 ± 0.5 and 2.0 ± 0.0 respectively for MOD1 and MOD4. No pre-embryonic mortality was recorded. The mean weight of the young guinea pigs of MOD1 (54.7 ± 10. g) was only 55% of that of MOD4 (98.6 ± 13.6 g). At weaning, the average weight gain of young guinea pigs of MOD1 (40.5 ± 22.2 g) represented a third of those obtained with other diets that did not significantly differ. At the end of RC, the weight gain of dams was 17 ± 13.3% for MOD1 compared to 50% for MOD2, MOD3 and MOD4. Feeding Panicum maximum alone induces chronic malnutrition which in turn is responsible of the low ovulation rate and reduced growth in guinea pig breeding.